Intelligent computing in engineering and architecture 13th EG-ICE Workshop 2006, Ascona, Switzerland, June 25-30, 2006: revised selected papers - EG-ICE Workshop (Lecture notes in computer science ;, 2006)
This book constitutes the thoroughly refereed proceedings of the 13th Workshop of the European Group for Intelligent Computing in Engineering on Intelligent Computing in Engineering and Architecture, EG-ICE 2006, held in Ascona, Switzerland in June 2006. The 59 revised full papers were carefully reviewed and selected from numerous submissions for inclusion in the book. In addition there is a summary of a panel session on the Joint International Conference on Computing and Decision Making in Civil and Building Engineering. All issues of advanced informatics are covered - in terms of current aspects of engineering - including a range of techniques such as artificial intelligence, evolutionary and adaptive computing, case based reasoning, networking and computer supported co-operative working, concurrent engineering, human computer interface issues, agents, constraint based reasoning, VR, and workflow design.